2012
DOI: 10.1309/ajcpyk60bzrnnahq
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up Outcomes in a Large Cohort of Patients With Human Papillomavirus–Negative ASC-H Cervical Screening Test Results

Abstract: Limited follow-up data are available on patients with cervical cytology results of atypical squamous cells, cannot exclude a high-grade intraepithelial lesion (ASC-H), who test negative for high-risk human papillomavirus (hrHPV). Between June 2005 and December 2010, 885 patients were identified with ThinPrep results of Hybrid Capture 2 (HC2) hrHPV-negative cervical ASC-H liquid-based cytology and follow-up histopathology or cytology results extending to September 2011. Of the 885 patients with available follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 55 publications
0
23
0
1
Order By: Relevance
“…Some authors have concluded that a negative HPV test result accompanying ASC-H offers a high negative predictive value, and suggest the possibility of cytology and HPV testing at follow-up in low-risk patients instead of colposcopy. However, the results of other studies do not support these findings: some HPV-negative ASC-H cases end up being ≥CIN II lesions [4,11]. In a meta-analysis by Xu et al [18], the pooled absolute sensitivity and specificity of the hybrid capture 2 (HC2) for ≥CIN II (in 19 studies) were 93 and 45%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some authors have concluded that a negative HPV test result accompanying ASC-H offers a high negative predictive value, and suggest the possibility of cytology and HPV testing at follow-up in low-risk patients instead of colposcopy. However, the results of other studies do not support these findings: some HPV-negative ASC-H cases end up being ≥CIN II lesions [4,11]. In a meta-analysis by Xu et al [18], the pooled absolute sensitivity and specificity of the hybrid capture 2 (HC2) for ≥CIN II (in 19 studies) were 93 and 45%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these, the majority of Pap smears can be assigned into specific categories [4]. ASC-H is an uncommon cytology interpretation with an estimated incidence of 0.27-0.56% [11]. The international recommendations indicate ASC-H cases should represent less than 10% of atypical cytologies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the current ASCCP and Korean guidelines recommend initial colposcopy with biopsy for women with Papanicolaou test (Pap test) results showing ASC-H, regardless of the HPV test results; however, there have been ongoing debates about the clinical significance and utility of the HPV test for the management of ASC-H [12][13][14].…”
Section: Introductionmentioning
confidence: 99%